Management of Major Limb Injuries - Vijay Langer (The Scientific World Journal)
Management of major limb injuries is a daunting challenge, especially as many of these patients have severe associated injuries. In trying to save life, often the limb is sacrificed. The existing guidelines on managing such trauma are often confusing. There is scope to lay down such protocols along with the need for urgent transfer of such patients to a multispecialty center equipped to salvage life and limb for maximizing outcome. This review article comprehensively deals with the issue of managing such major injuries.